Biogeographical patterns among deep sea megabenthic communities across the Drake Passage. Issue 6 (31st July 2017) - Auscavitch, Steven R.; Waller, Rhian G.
Abstract: Biogeographical patterns among deep sea benthic communities in the Drake Passage remain poorly understood as a consequence of poor sampling resolution and the spatial remoteness of many sea floor features. Hard-bottom features, including at least 20 seamounts, remain uncharacterized with respect to their benthic megafaunal community assemblages. Here, we present community assemblage patterns from several locations across the Drake Passage to better understand the faunal relationships between deep sea floor communities in the region. Towed camera surveys were conducted on nine topographical features ranging from shelf environments on the southern Chilean Margin, the western Antarctic Peninsula shelf and seamounts in the central Drake Passage. These are the first quantitative measurements of megafaunal abundance at two seamount complexes in the central Drake Passage and multivariate analyses are used to examine the factors influencing species distributions. Three biogeographical groupings were identified based on species assemblages and environmental variables specific to major water mass boundaries in the region: sub-Antarctic Mode Water (318–523 m), Antarctic Intermediate Water (504–1128 m) and Circumpolar Deep Water (1837–3034 m). Further examination of megafaunal associations between sea floor structures may provide clues as to how sub-Antarctic communities are connected throughout the greater Southern Ocean.